Determinan Kualitas Audit dalam Perspektif Auditor Indonesia - Wali Saputra (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2022)
This study aims to analyze the effect of independence, professional ethics, due professional care, and professional skepticism on audit quality. This study uses primary data obtained by distributing questionnaires to 105 auditors who work in public accountant firms in Indonesia. Data analysis methods used in this study include research instrument testing, classical assumption testing and hypothesis testing using multiple linear regression analysis. The results showed in the F test (simultaneous) that the independence of professional ethical auditors, due professional care, and professional skepticism simultaneously affect audit quality with a sig F value of 0.000 <0.05 and F count of 47.740 and an R Square value of 65.6%. The results of the t test (partial) show that independence affects audit quality with a sig t value of 0.001 <0.05, professional ethics has an effect on audit quality with a sig t value of 0.000 <0.05, due professional care has an effect on audit quality with a sig t value of 0.025 < 0.05 , and professional skepticism has an effect on audit quality with a sig t value of 0.004 < 0.05 So, it can be concluded that independence, professional ethics, due professional care, and professional skepticism simultaneously affect audit quality.